2010
DOI: 10.2110/jsr.2010.076
|View full text |Cite
|
Sign up to set email alerts
|

How Did Thin Submarine Debris Flows Carry Boulder-Sized Intraclasts for Remarkable Distances Across Low Gradients to the Far Reaches of the Mississippi Fan?

Abstract: Submarine density flows dominate sediment transport into many parts of the ocean and form submarine fans, which are some of the largest sediment accumulations on Earth. Previous studies often assumed that the distal fringes of submarine fans would be dominated by extensive sheet-like deposits from dilute and expanded turbidity currents, because only turbidity currents would transport large volumes of sediment for long distances across such low gradients. Deposits with a remarkable frondlike shape occur at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 48 publications
3
66
0
Order By: Relevance
“…Such hybrid or linked turbidite-debrite beds were described previously (e.g., Wood and Smith, 1958;Middleton, 1979, 1980;RicciLucchi and Valmori, 1980;Zeng et al, 1991), but only recently has it become apparent that they are common in many locations worldwide (Haughton et al, 2003(Haughton et al, , 2009Sylvester and Lowe, 2004;Talling et al, 2004Talling et al, , 2007cTalling et al, , 2010Amy and Talling, 2006;Ito, 2008;Zeng et al, 1991;Amy et al, 2009;Hodgson, 2009;Jackson et al, 2009;Pyles and Jennette, 2009;Muzzi Magalhaes and Tinterri, 2010). Understanding these hybrid fl ows is important because they are a common feature of the most important processes for delivering sediment to the deep ocean.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Such hybrid or linked turbidite-debrite beds were described previously (e.g., Wood and Smith, 1958;Middleton, 1979, 1980;RicciLucchi and Valmori, 1980;Zeng et al, 1991), but only recently has it become apparent that they are common in many locations worldwide (Haughton et al, 2003(Haughton et al, , 2009Sylvester and Lowe, 2004;Talling et al, 2004Talling et al, , 2007cTalling et al, , 2010Amy and Talling, 2006;Ito, 2008;Zeng et al, 1991;Amy et al, 2009;Hodgson, 2009;Jackson et al, 2009;Pyles and Jennette, 2009;Muzzi Magalhaes and Tinterri, 2010). Understanding these hybrid fl ows is important because they are a common feature of the most important processes for delivering sediment to the deep ocean.…”
Section: Introductionmentioning
confidence: 79%
“…6A, 6B) may have been supported because they are less dense than the surrounding matrix. A more detailed analysis of clast support in cohesive debris fl ows was provided in Talling et al (2010). This type of intermediate strength debris fl ow is broadly simi lar to intermediate strength debris fl ows responsible for thicker clast-rich debrites (e.g., Piper et al, 1999;Laberg and Vorren, 2000;Tripsanas et al, 2008), but it has a lower strength that permits a longer runout across low gradients.…”
Section: Origin Of Clast-rich (Higher Strength) Cohesive Debritesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, distal lobe deposits can also show abrupt thickness variations along-strike indicating a finger-like "dendritic" pattern (Twichell et al, 27 1992;PrĂ©lat et al, 2009;Talling et al, 2010) rather than a simple radial sheet commonly found in schematic models (Mutti and Normark, 1987). The low thinning rate values from distal locales ( Figure 7) suggests that neither the Point Loma nor the compiled distal lobe deposits contain these dendritic features, or that they are not sampled or recognized within the extent of the outcrops and within the database.…”
Section: Intra-lobe Element Bed Architecture: Analysismentioning
confidence: 99%
“…However, detailed fieldwork on land and in the oceans by correlating beds across large distances has shown that the opposite can also happen, with densification of turbidity currents or embedded debris flow layers leading to depositing denser flows such as debris flows [268,269]. The high density of debris flows may also explain how some large boulders can be carried as far as the distal parts of fans [270]. These and many other issues have been addressed by UK groups with laboratory and numerical simulation of sedimentary flows [271][272][273][274][275][276].…”
Section: (F ) Continental Slopes and Gravity-driven Sediment Transportmentioning
confidence: 99%